National Early Warning Score 2 (NEWS2) as a prognostic tool for adult patients in emergency department: A retrospective observational study - Nor Safiahani Mhd Yunin; Toh Leong Tan (PLoS ONE, 2025)
The National Early Warning Score 2 (NEWS2) has been widely adopted to assess the severity of illness across various healthcare settings. However, its effectiveness as a prognostic tool specifically within the Emergency Department (ED) has not been validated in Malaysia. This retrospective observational study aimed to evaluate the performance of NEWS2 in predicting hospitalizations, critical care unit admissions, and in-hospital mortality among adult patients in a Malaysian ED, specifically at the Hospital Canselor Tuanku Muhriz. The discriminatory ability of NEWS2 was analysed using the area under the receiver operating characteristic curve. A total of 1906 adult patients were included in the study, with results indicating that NEWS2 demonstrated moderate to excellent performance in predicting outcomes. The AUROC values were 0.71 for hospitalization, 0.75 for critical care admission, and 0.86 for in-hospital mortality. Additionally, subgroup analyses for patients with sepsis and those with COVID-19 were also conducted. NEWS2 score however was not as effective in predicting critical outcomes for these two subgroups, limiting its utility as an early warning tool in diverse clinical scenarios. Overall, the results suggest that NEWS2 is a valuable tool for early risk stratification in the general adult population in the ED. Implementing NEWS2 into routine clinical practice could significantly enhance patient outcomes by promoting timely and informed decision-making, ultimately benefiting both patients and healthcare providers.